PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA DINAS KEARSIPAN PROVINSI SUMATERA SELATAN - Dwi Pratiwi, Elsi; Roni , Mukran (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
The purpose of this study was to determine the effect of discipline and motivation on employee performance at the Archives Office of South Sumatra province. The data analysis technique used in this research is quantitative. In this research, several types data collection were used, namely observation, questionnaires, documentaries and literature studies. The sample and population were 42 respondents. Work discipline and motivation havean overall influence on employee performance the South Sumatra Province Archives Service. This is evidenced by the output of SPSS version 22 which shows the value obtained jointly for the variables of work discipline and work motivation, namely 0.717 or reaching 71.7%. This leaves 28.3% influenced by other factors that researchers did not include in this study. Based on the F test it is also concluded that the significance value obtained is less than 0.05, namely 0.000 so that there is simultaneous relationship between work discipline and work motivation on employee performance at the Archives Office of South Sumatra Province. The results show that work discipline has positive effect the work motivation of the Archives Office of South Sumatra Province and work motivation has positive effect on the work performance of the Archives Office of South Sumatra Province.